Synthesis, structural, optical, morphological and multi sensing properties of graphene based thin film devices. (1st August 2018) - Rahim, Ishrat; Shah, Mutabar; Iqbal, Mahmood; khan, Afzal
Abstract: This research article represents the synthesis, structural, optical, morphological and sensing properties of graphene (G) based thin film devices. The sensor was fabricated on a substrate with pre-deposited interdigitated copper electrodes. The UV-Visible spectroscopy of the aqueous solution of graphene confirmed the formation of graphene, furthermore, the optical band gap energy value calculated from the spectrum yielded to be 2.5 eV. The fabricated thin film of graphene was characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD) and Raman spectroscopy. The humidity sensing properties of the sensor were investigated by exposing it to a wide humidity range (5%–95%RH) at 25 ºC. It was observed that the relative capacitance was increased by 700, 600, 500, 124.8 and 42.6 times at 0.1, 0.5, 1, 5 and 10 kHz, respectively. While the resistance was decreased by. 01, 0.012, 0.02, 0.08 and 0.16 times at 0.1, 0.5, 1, 5 and 10 kHz, respectively. Compared with traditional humidity sensors, the graphene sensor demonstrated an ultrahigh sensitivity and a rapid response/recovery time in wide humidity range. The hysteresis curve measurement showed that the device has a minimum power loss and high stability. The fabricated sensor was also used for the detection of different gases such as ammonia, ethanol and methanol. It was observed from the experimentally obtained result that the sensor is highly sensitive to ammonia as compared to other two gases. In addition, the temperature sensing abilities of the thin film sensor has also been evaluated. These observed results demonstrate that graphene is promising material of candidate for constructing highly stable and rapid multifunctional sensors in widespread applications.